Inadimplência das famílias brasileiras e educação financeira no Ensino Médio: evidência de descompasso (Revista Lusófona de Educação, 2026)
Brazilian household delinquency followed an upward trajectory between 2022 and 2025, with a predominance of debts linked to banks/credit cards, recurring bills (utilities), and finance companies, reinforcing the need for school financial education connected to real situations of credit, consumption, and indebtedness. This article investigates the extent to which the financial mathematics content included in the curricular projects of Integrated Secondary Education at the Federal Institute of São Paulo aligns with the recent profile of delinquency. This is a documentary case study based on the “Mapa da inadimplência e renegociação de dívidas no Brasil” and the analysis of 102 curricular projects from 37 campuses. Between January 2022 and December 2025, the estimated number of delinquent consumers increased by 16.38 million, and the rate rose from 40.30% to 49.77%, with greater concentration among individuals aged 26 to 60 and a relative increase in the population aged 60 and older. In the curricular projects, financial mathematics, simple interest, and compound interest predominate, whereas rate equivalence, amortization, inflation, and investments appear infrequently. It is concluded that a mismatch persists between the complexity of indebtedness and the depth of curricular projects, reinforcing the need for curricular revision and the use of real data in critical financial education practices.Keywords: Financial education; Indebtedness; Curriculum